by **pster** » Wed Feb 06, 2013 2:45 pm

Here is how I think these can be derived. There is probably a typo or two. If you catch one, please let me know. My eyes glaze over anymore when I look at these. Also, one can quibble with comma placement.

Call the two sentences that are to be joined by the conjunction P and Q.

In each case we need a copula (is) and a neuter demonstrative (that/those). We can call our relative pronoun which.

The main move employed in some, but not all, may seem like a slight of hand, but I think it is correct. It took me a couple of days to figure out how to get the conjunctions to go in the right direction. However, it is important to note that there are some subtle differences between the derivations.

The interesting moral of the story is that when you see one of these conjunctions, the relative pronoun in the conjunction often, but not in all cases, originally referred to the proposition that directly follows it.

If that seems puzzling, something that may or may not make it less puzzling is the idea that a conjunction like good old English "that" is regarded in (formal) semantics as being originally a demonstrative pronoun. Consider: "Jane said that Bill was tired." One can think of the "that" as just pointing ostensively at the sentence "Bill was tired". So: Jane said that! <point finger at>>>> "Bill was tired."

----------------

ἐξ οὗ: since

According to Sidgwick, this is a temporal sense and it is the main way to say "since" in Greek (and it takes the indicative.)

P is that, from which Q = P, from which Q = from which (namely P), Q = since P, Q

Alternatively,

P is that, ἐξ οὗ Q = P, ἐξ οὗ Q = ἐξ οὗ (namely P), Q = ἐξ οὗ P, Q = since P, Q

---------------------

ἀφ' οὗ: since

Should be identical to the preceding.

-------------------

ἐν ᾧ: while

P is at that moment, at which moment Q = at which moment (namely at the moment of P) Q = at which moment (namely the moment of P), Q = while P, Q

Alternatively,

P is at that moment, ἐν ᾧ Q = ἐν ᾧ (namely at the moment of P), Q = ἐν ᾧ (namely the moment of P), Q = ἐν ᾧ P, Q = while P, Q

One can also imagine these being derived with an extra preposition.

P is ἐν τούτῳ, ἐν ᾧ Q = ἐν ᾧ (namely ἐν ᾧ P), Q = ἐν ᾧ P, Q

I am not sure which derivation is correct. And I am not sure whether "P is ἐν τούτῳ" is correct Greek. Can we have a predicate dative of time with a copula like that?

However that may be, it is worth noting that most of these derivations do not make use of an extra preposition.

-----------------------

εἰς ὅ: till

P is that, up to that Q = P, up to that Q = up to that (namely P), Q = till P, Q

Alternatively,

P is that, εἰς ὅ Q = P, εἰς ὅ Q = εἰς ὅ (namely P), Q = till P, Q

--------------------------

μέχρι (ἄχρι) οὗ: until

P is that, as far as which Q = P, as far as which Q = as far as which (namely P), Q = until P, Q

Alternatively,

P is that, μέχρι οὗ Q = P, μέχρι οὗ Q = μέχρι οὗ (namely P), Q = μέχρι οὗ P, Q = until P, Q

-----------------------------

ἀνθ' ὧν: because OR therefore

Smyth says it means "because". But LSJ list "therefore" as the first meaning and "because" as the second:

—hence “ἀνθ᾽ ὧν” wherefore, A.Pr.31, S.OT264, Th.6.83, Ev.Luc.12.3; “ἀντὶ τούτου” therefore, Ep.Eph.5.31; but ἀνθ᾽ ὧν also for ἀντὶ τούτων ὄτι . ., because, S.Ant. 1068, Ar.Pl.434

ἀνθ' ὧν: therefore (CASE 1)

P is that, in return for which Q = P, in return for which Q = P, therefore Q

Alternatively,

P is that, ἀνθ' ὧν Q = P, ἀνθ' ὧν Q = P, therefore Q

ἀνθ' ὧν: because (CASE 2)

LSJ indicates how this works.

ἀντὶ τούτων ὅτι P, Q = ἀνθ' ὧν P, Q = because P, Q

I only give one derivation here because I don't have an extra English word for ὅτι.

-------------------------------------

ἐξ ὧν: because

P are those, from which Q = P, from which Q = from which (namely P), Q = because P, Q

Alternatively,

P are those, ἐξ ὧν Q = P, ἐξ ὧν Q = ἐξ ὧν (namely P), Q = ἐξ ὧν P, Q = because P, Q

---------------------------

ἐφ' ᾧτε: on condition that

P is that, upon which Q = P, upon which Q = upon which (namely P), Q = upon which (namely P), Q = on condition that P, Q

Alternatively,

P is that, ἐφ' ᾧτε Q = P, ἐφ' ᾧτε Q = ἐφ' ᾧτε (namely P), Q = ἐφ' ᾧτε P, Q = on condition that P, Q

The example from Smyth 2279 mentioned above illustrates a later manipulation/development.